Videoendoscope-guided fluorescein-assisted vitrectomy for phakic malignant glaucoma. - Chen, S; Salmon, J; Patel, C (2005)
Malignant glaucoma is a rare secondary glaucoma classically occurring after intraocular surgery in eyes with primary angle closure. Pars plana vitrectomy is reserved for the treatment of malignant glaucoma when medical and laser treatment fail. The primary aim of surgery is the removal of the anterior vitreous to reduce resistance to aqueous flow into the anterior chamber. In phakic eyes, conventional pars plana vitrectomy without lens extraction is frequently unsuccessful because of difficulty visualizing the normally transparent anterior vitreous, combined with the technical challenge of removing the anterior vitreous without damaging the crystalline lens. We describe a technique of intraocular, videoendoscope-guided, fluorescein-assisted pars plana vitrectomy that enables direct visualization and thorough removal of the anterior vitreous without the need for lens extraction in prepresbyopic patients without cataract.